Source dynamics of Ruapehu’s 2022 volcanic unrest: insights from drumbeat seismicity, tremor, and crater lake signals - Liam A. Bramwell; Finnigan Illsley-Kemp; Ery C. Hughes; Sophie Butcher; Oliver D. Lamb; Yannik Behr (Bulletin of Volcanology, 2025)
Ruapehu, one of Aotearoa New Zealand’s most active andesitic volcanoes, experienced moderate to heightened volcanic unrest beginning March 2022. This included heightened volcanic tremor, the initiation of a new heating phase at the crater lake Te Wai ā-moe, and increases in gas emissions. The unrest featured highly periodic, low-frequency earthquakes known as ‘drumbeats’. These signals have been observed around the world to often precede and/or accompany the ascent of magma and volcanic eruptions. However, Ruapehu did not erupt in 2022. In this work, approximately 43,000 discrete drumbeat events and 89 days of continuous volcanic tremor were identified over the 121-day unrest period. These were analysed in the time, amplitude, and frequency domains. We argue that increases in volcanic tremor, lake temperatures, and gas throughput are the result of magma ascent into the shallow system immediately prior to or contemporaneous with the onset of tremor. We construct a conceptual model for the generation of drumbeat, tremor, and lake temperature signals that consists of shallow magma storage, a gas cavity, a permeable cap, and the crater lake. The presence of repetitive drumbeat earthquakes results from transient sealing and failure within the fracture pathways of the permeable cap. This is driven and regulated primarily by pressure accumulation from persistently degassing magma and the strength of the sealing mechanism.

Conceptualizing a load and volume autoregulation integrated velocity model to minimize neuromuscular fatigue and maximize neuromuscular adaptations in resistance training - Landyn M. Hickmott; Scotty J. Butcher; Philip D. Chilibeck (European Journal of Applied Physiology, 2025)

Correction: Metabolic skinflint or spendthrift? Insights into ground sloth integument and thermophysiology revealed by biophysical modeling and clumped isotope paleothermometry - Michael D. Deak; Warren P. Porter; Paul D. Mathewson; David M. Lovelace; Randon J. Flores; Aradhna K. Tripati; Robert A. Eagle; Darin M. Schwartz; Michael T. Butcher (Journal of Mammalian Evolution, 2025)

Metabolic skinflint or spendthrift? Insights into ground sloth integument and thermophysiology revealed by biophysical modeling and clumped isotope paleothermometry - Michael D. Deak; Warren P. Porter; Paul D. Mathewson; David M. Lovelace; Randon J. Flores; Aradhna K. Tripati; Robert A. Eagle; Darin M. Schwartz; Michael T. Butcher (Journal of Mammalian Evolution, 2025)
Remains of megatheres have been known since the 18th -century and were among the first megafaunal vertebrates to be studied. While several examples of preserved integument show a thick coverage of fur for smaller ground sloths living in cold climates such as Mylodon and Nothrotheriops , comparatively very little is known about megathere skin. Assuming a typical placental mammal metabolism, it was previously hypothesized that megatheres would have had little-to-no fur as they achieved giant body sizes. Here the “hairless model of integument” is tested using geochemical analyses to estimate body temperature to generate novel models of ground sloth metabolism, fur coverage, and paleoclimate with Niche Mapper software. The simulations assuming metabolic activity akin to those of modern xenarthrans suggest that sparse fur coverage would have resulted in cold stress across most latitudinal ranges inhabited by extinct ground sloths. Specifically, Eremotherium predominantly required dense 10 mm fur with implications for seasonal changes of coat depth in northernmost latitudes and sparse fur in the tropics; Megatherium required dense 30 mm fur year-round in its exclusive range of cooler, drier climates; Mylodon and Nothrotheriops required dense 10–50 mm fur to avoid thermal stress, matching the integument remains of both genera, and further implying the use of behavioral thermoregulation. Moreover, clumped isotope paleothermometry data from the preserved teeth of four genera of ground sloth yielded reconstructed body temperatures lower than those previously reported for large terrestrial mammals (29 ± 2°–32 ± 3° C). This combination of low metabolisms and thick fur allowed ground sloths to inhabit various environments.

Shear Strength of a Large Limestone Discontinuity: In Situ Pull Test and Prediction - Clarence Butcher; Olivier Buzzi; Anna Giacomini; Robert Bertuzzi; D. V. Griffiths; Stephen Fityus (Rock Mechanics and Rock Engineering, 2025)

Interactions between White Sharks (Carcharodon carcharias) and artificial reefs along the east-coast of Australia - Alistair Becker; Paul A. Butcher; Stephen Morris; Curtis Champion; Victor M. Peddemors; Michael B. Lowry; Matthew D. Taylor (Fisheries Research, 2024)

Illegal killing associated with gamebird management accounts for up to three-quarters of annual mortality in Hen Harriers Circus cyaneus - Steven R. Ewing; Cathleen E. Thomas; Nigel Butcher; Blánaid Denman; David J.T. Douglas; David I.K. Anderson; Guy Q.A. Anderson; James Bray; Steve Downing; Ronan Dugan; Brian Etheridge; Will Hayward; et al. (Biological Conservation, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A pilot safety, tolerability and pharmacokinetic study of an oro-buccal administered cannabidiol-dominant anti-inflammatory formulation in healthy individuals: a randomized placebo-controlled single-blinded study - Luis Vitetta; Belinda Butcher; Jeremy D. Henson; David Rutolo; Sean Hall (Inflammopharmacology, 2021)

The effectiveness of Shark‐Management‐Alert‐in‐Real‐Time (SMART) drumlines as a tool for catching white sharks, Carcharodon carcharias , off coastal New South Wales, Australia - Rick D. Tate; Brendan P. Kelaher; Craig P. Brand; Brian R. Cullis; Christopher R. Gallen; Stephen D.A. Smith; Paul A. Butcher (Fisheries Management and Ecology, 2021)
White ( Carcharodon carcharias L.), bull ( Carcharhinus leucas , Müller & Henle) and tiger ( Galeocerdo cuvier , Péron & Lesueur) sharks are the primary species responsible for unprovoked shark bites. Historically, management practices were based on culling “target” shark species (i.e. white, bull and tiger sharks), which resulted in high levels of bycatch and mortality. Shark‐Management‐Alert‐in‐Real‐Time (SMART) drumlines were trialled in New South Wales, Australia, aiming to optimise the capture of target shark species while minimising bycatch and mortality. Target shark species accounted for 70% of the total catch, with white sharks contributing 298 of the 350 sharks that were caught. Four animals died, and bycatch consisted of 13 species including two threatened species. Generalised linear mixed models (GLMMs) revealed a significant spatial, temporal, environmental and gear influence on white shark catch rates. SMART drumlines are a useful tool for catching target shark species with low bycatch and mortality relative to historical bather protection methods.

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

A robust machine learning framework to identify signatures for frailty: a nested case-control study in four aging European cohorts - David Gomez-Cabrero; Stefan Walter; Imad Abugessaisa; Rebeca Miñambres-Herraiz; Lucia Bernad Palomares; Lee Butcher; Jorge D. Erusalimsky; Francisco Jose Garcia-Garcia; José Carnicero; Timothy C. Hardman; Harald Mischak; Petra Zürbig; et al. (GeroScience, 2021)

Determining effective acoustic array design for monitoring presence of white sharks Carcharodon carcharias in nearshore habitats - Sofia M. Gabriel; T. A. Patterson; J. P. Eveson; J. M. Semmens; D. Harasti; P. A. Butcher; J. L. Y. Spaet; R. W. Bradford (Marine Biology, 2021)

Molecular phylogeny places the enigmatic subfamily Masoninae within the Ichneumonidae, not the Braconidae - Donald L. J. Quicke; Andrew D. Austin; Erinn P. Fagan‐Jeffries; Paul D. N. Hebert; Buntika A. Butcher (Zoologica Scripta, 2020)
The Masoninae (type genus Masona van Achterberg) is a widespread but seldom collected group of morphologically aberrant tiny (body length 2 mm or less) wasps that have always been considered as a subfamily of Braconidae, albeit on little supporting evidence. Discovery of a fully winged female of Masona from remote Australia has enabled a reassessment of its relationships. This specimen yielded sequence data for the nuclear 28S and 18S rDNA genes, the barcoding fragment of mitochondrial cytochrome oxidase subunit 1 and the mitochondrial 16S rDNA gene. These were analysed separately and together, along with representatives of Braconidae and Ichneumonidae. Maximum likelihood analyses of all four genes separately and combined concur that Masona is nested within the Ichneumonidae and, therefore, is not a member of Braconidae. This is also supported by the position of the sternaulus low on mesopleuron, absence of fore wing vein (RS + M)a (though the great reduction in wing venation makes further interpretation problematic) and the articulated junction of metasomal tergites 2 and 3. On balance, molecular analyses place Masona basally among the ophioniformes lineage of Ichneumonidae. Formal description of the Australian species as Masona timpaynei Quicke sp. n. and a revised diagnosis of Masoninae are provided in S1 together with illustration of the holotype.

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Architectural Properties of Sloth Forelimb Muscles (Pilosa: Bradypodidae) - Rachel A. Olson; Zachary D. Glenn; Rebecca N. Cliffe; Michael T. Butcher (Journal of Mammalian Evolution, 2018)

Improving reliability of species identification and logbook catch reporting by commercial fishers in an Australian demersal shark longline fishery - W. G. Macbeth; P. A. Butcher; D. Collins; S. P. McGrath; S. C. Provost; A. C. Bowling; P. T. Geraghty; V. M. Peddemors (Fisheries Management and Ecology, 2018)
Large adult carcharhinid and sphyrnid sharks have been targeted in coastal waters off New South Wales, eastern Australia, by commercial fishers using demersal longlines since 2005. Inaccurate fisher reporting of the composition of catches led in 2008 to a range of complementary management measures to help improve reliability, including a redesigned catch logbook, species identification guide and at‐sea education via an observer programme. This study provides results from assessments of the effectiveness of those measures. A questionnaire yielded overwhelmingly positive feedback from fishers regarding the usefulness of the species identification guide. Comparison of observer‐recorded data and corresponding fisher‐reported logbook data via weighted linear mixed‐effects modelling found that since 2008, misreporting of catches has varied considerably among species and, for some species, among fishers. With some species commonly under‐reported and others frequently over‐reported, it is apparent that certain species were likely mistaken for other morphologically similar species. Such systematic error inherently undermines stock assessments of these vulnerable species. Management strategies designed to include education and extension will ensure greater reliability of fisher reporting of shark catches in the future.

Functional Morphology of the Forelimb of the Nine-Banded Armadillo (Dasypus novemcinctus): Comparative Perspectives on the Myology of Dasypodidae - R. A. Olson; M. D. Womble; D. R. Thomas; Z. D. Glenn; M. T. Butcher (Journal of Mammalian Evolution, 2016)

Influences of twine diameter and mesh area on the efficiency and durability of baited hoop nets targeting portunids - M. K. Broadhurst; P. A. Butcher; B. R. Cullis; D. J. Tolhurst (Fisheries Management and Ecology, 2015)
The utility of varying twine diameter (0.5–0.8 mm Ø) and/or mesh area (0.5:1) in south‐eastern Australian recreational hoop nets was assessed in response to concerns over (1) impacts to discarded, undersize Scylla serrata L. and Portunus pelagicus Forskål and (2) marine debris (lost meshes). There was a negative relationship between Ø and breakage, with more in the narrowest (16.16–18.42 meshes deployment −1 ) than thickest (8.79–4.68) twines. Mesh damage was also affected by interactions between netting area and (1) soak time (only S. serrata ) and (2) catches, with all nets similarly damaged during S. serrata catches, but was negatively associated with catches of P. pelagicus , while the small‐area nets caught proportionally (to area) fewer portunids. The results reflect species‐ and size‐specific behavioural variability, but support using thick twine and limiting deployment durations for hoop nets. Alternatively, other less controversial traps might offer a more holistic solution to the stated concerns.

Age and growth of mangrove red snapper Lutjanus argentimaculatus at its cool‐water‐range limits - T. P. Piddocke; G. L. Butler; P. A. Butcher; J. Stewart; D. J. Bucher; L. Christidis (Journal of Fish Biology, 2015)
This study investigates the age and growth of Lutjanus argentimaculatus at its southern (cooler) range limits in eastern Australia. Specimens were collected from New South Wales and southern Queensland between November 2011 and December 2013. Fork lengths ( L F ) ranged from 190 to 1019 mm, and ages ranged from 2+ to 57+ years. Growth was described by the von Bertalanffy growth function with coefficients L ∞ = 874·92 mm, K = 0·087 year −1 and t 0 = −2·76 years. Estimates of the instantaneous natural mortality rate ( M ) ranged from 0·072 to 0·25. The L F (mm) and mass ( W ; g) relationship was represented by the equation: . The maximum age of 57+ years is the oldest reported for any lutjanid and comparisons with tropical studies suggest that the age‐based demography of L. argentimaculatus follows a latitudinal gradient. High maximum ages and low natural mortality rates indicate considerable vulnerability to overexploitation at the species' cool‐water‐range limits. These results demonstrate the need to identify underlying processes driving latitudinal gradients in fish demography.

Strategic taxonomy in a biodiverse landscape: a novel approach to maximizing conservation outcomes for rare and poorly known flora - Juliet A. Wege; Kevin R. Thiele; Kelly A. Shepherd; Ryonen Butcher; Terry D. Macfarlane; David J. Coates (Biodiversity and Conservation, 2015)

Spatial and temporal patterns of range expansion of white‐winged doves in the USA from 1979 to 2007 - Jerrod A. Butcher; Bret A. Collier; Nova J. Silvy; Jay A. Roberson; Corey D. Mason; Markus J. Peterson (Journal of Biogeography, 2014)
Aim The geographical expansion of white‐winged doves ( Zenaida asiatica ) in North America has attracted the attention of biologists and sportsmen because of their recreational and aesthetic value; however, data on factors driving the spatial spread of this species are lacking. We examined spatial and temporal patterns of range expansion for white‐winged doves along the northern edge of their geographical range from 1979 to 2007 and used a dynamic occupancy model to estimate when and where doves would be found along an expansion gradient. Location Southern half of the USA . Methods We modelled spatial variation in the range expansion of white‐winged doves from 1979 to 2007 using data from the North American Breeding Bird Surveys ( BBS ) and distance from initial population centre, area of urban land cover, and ecoregion. We used a robust design occupancy analysis to estimate species expansion rate based on a model set grounded in broad‐scale conditions likely to drive dove distribution. We evaluated our best fitting model (using Akaike's information criterion adjusted for small sample size) by comparing estimates to actual observations in 1993 and 2007 using area under the curve ( AUC ) metrics from receiver‐operating characteristic plots. Results Our spatial distribution model indicated that range expansion of white‐winged doves was primarily influenced by distance from the core population centre, with additive effects of ecoregion and land cover. In 1979, white‐winged doves were present in 12% of survey locations, whereas presence increased to 41% by 2007. Across all ecoregions, urban land cover was positively related to probability of occupancy. We evaluated our model for 1993 and 2007 by comparing derived occupancy estimates to sightings of white‐winged doves within our sample hexagons using BBS survey data. Based on high AUC statistics (> 0.85), we concluded that our model was useful for accurately predicting range expansion. Main conclusions Estimating occurrence and range expansion of white‐winged doves and other expanding/invasive avian species at large spatial scales can be effectively conducted using BBS data. Using these nationwide, long‐term survey data to relate expansion to a suite of conditions likely to drive population dynamics is an effective approach to developing predictive models of range expansion.

The nitrate time bomb: a numerical way to investigate nitrate storage and lag time in the unsaturated zone - L. Wang; A. S. Butcher; M. E. Stuart; D. C. Gooddy; J. P. Bloomfield (Environmental Geochemistry and Health, 2013)

Limited pollen-mediated dispersal and partial self-incompatibility in the rare ironstone endemic Tetratheca paynterae subsp. paynterae increase the risks associated with habitat loss - P. A. Butcher; D. Bradbury; S. L. Krauss (Conservation Genetics, 2011)

Assessing the effects of line capture and barotrauma relief procedures on post‐release survival of key tropical reef fish species in Australia using recreational tagging clubs - W. D. SUMPTON; I. W. BROWN; D. G. MAYER; M. F. McLENNAN; A. MAPLESTON; A. R. BUTCHER; D. J. WELCH; J. M. KIRKWOOD; B. SAWYNOK; G. A. BEGG (Fisheries Management and Ecology, 2010)
Common coral trout, Plectropomus leopardus Lacepède, crimson snapper, Lutjanus erythropterus Bloch, saddletail snapper, Lutjanus malabaricus (Bloch & Schneider), red emperor, Lutjanus sebae (Cuvier), redthroat emperor, Lethrinus miniatus (Schneider) and grass emperor, Lethrinus laticaudis Alleyne & Macleay, were tagged to determine the effects of barotrauma relief procedures (weighted shot‐line release and venting using a hollow needle) and other factors on survival. Release condition was the most significant factor affecting the subsequent recapture rate of all species. Capture depth was significant in all species apart from L. malabaricus and L. miniatus , the general trend being reduced recapture probability with increasing capture depth. Recapture rates of fish hooked in either the lip or mouth were generally significantly higher than for those hooked in the throat or gut. Statistically significant benefit from treating fish for barotrauma was found in only L. malabaricus , but the lack of any negative effects of treating fish indicated that the practices of venting and shot‐lining should not be discouraged by fisheries managers for these species.

Influence of terminal rig configuration on the anatomical hooking location of line‐caught yellowfin bream, Acanthopagrus australis - P. A. BUTCHER; M. K. BROADHURST; D. REYNOLDS; S. C. CAIRNS (Fisheries Management and Ecology, 2008)
Experiments were carried out to test the dependence of anatomical hooking location on terminal rig configuration, and identify strategies by which hook ingestion can be minimised to reduce post‐release mortality of angled yellowfin bream, Acanthopagrus australis (Günther). Eighty‐five anglers targeted yellowfin bream using different designs and sizes of circle and J hooks and recorded technical, environmental and biological data for each landed fish. Considerably fewer fish (16.6 and 8.5%, respectively) ingested hooks than those hooked in the mouth (82.1 and 88.6%), and a greater percentage of J hooks were ingested than circle hooks or a J hook modified with a 15‐mm horizontal bar. Irrespective of hook type, the rate of ingestion also declined with increasing hook weight and decreasing fish size. In cage experiments, significantly more hooks baited with natural soft baits (e.g. intestines and cephalopods) were ingested than those baited with artificial baits, crustaceans or teleosts, while in the field fewer hooks were ingested using artificial bait (e.g. bread and pellets) than terrestrial animals, teleosts, crustaceans, teleost or terrestrial animal intestines, cephalopods or polychaetes. Similarly, rigs with floats, short traces or a sinker only on the hook, along with angling in environments with at least some current reduced ingestion. Based on this study, anglers targeting yellowfin bream should be encouraged to use circle or modified J hooks and, regardless of the hook design, the largest hook size possible attached to short traces or a sinker only and hard baits.

Scale pattern analysis is preferable to OTC marking of otoliths for differentiating between stocked and wild dusky flathead, Platycephalus fuscus , and sand whiting, Sillago ciliata - A. Butcher; D. Mayer; D. Willett; M. Johnston; D. Smallwood (Fisheries Management and Ecology, 2003)
A pilot programme to evaluate the effect of stocking dusky flathead, Platycephalus fuscus (Cuv. & Val.), and sand whiting, Sillago ciliata (Cuv. & Val.), began in the Maroochy River estuary in 1995. Two possible methods of mass marking; oxytetracycline (OTC) marking of otoliths, and scale pattern analysis (SPA) were investigated. A range of OTC trials was conducted, with limited success. High concentrations (1000 mg L −1 ) of OTC and low salinities (≤9°/ 00 ) produced acceptable marks on the otoliths of both species, but at the expense of fingerling survival and environmental health risks. SPA provided better results, with wild to hatchery misclassification rates of 25 and 11%, respectively, for P. fuscus and S. ciliata . The reverse misclassification rate of hatchery to wild was equal or better for both species. Field trials demonstrated that SPA was able to differentiate between the two sources of fingerlings (wild and hatchery). These results indicated that OTC was impractical, while SPA was acceptable for this pilot programme. The implications of these results are discussed.

Improving linkage analysis in outcrossed forest trees – an example from Acacia mangium - P. Butcher; E. Williams; D. Whitaker; S. Ling; T. Speed; G. Moran (Theoretical and Applied Genetics, 2002)

Influence of Environmental Contamination with PCBs on Human Health - D. Orlinskii; I. Priputina; A. Popova; A. Shalanda; T. Tsongas; G. Hinman; W. Butcher (Environmental Geochemistry and Health, 2001)

Stratigraphical distribution of platinum-group minerals in the Eastern Layered Series, Rum, Scotland - M. R. Power; D. Pirrie; J. C. Ø. Andersen; A. R. Butcher (Mineralium Deposita, 2000)

Molecular evidence for multiple infections of a new subgroup of Wolbachia in the European raspberry beetle Byturus tomentosus - G. Malloch; B. Fenton; R. D. J. Butcher (Molecular Ecology, 2000)
Wolbachia , a group of maternally inherited intracellular parasitic bacteria, alter host reproduction, including the induction of thelytokous parthenogenesis, feminization of genetic males, son killing and, most commonly, the induction of cytoplasmic incompatibility (CI), in a diverse array of arthropods. CI can result in infertility and has attracted attention because of its potential in biological control and as an agent in speciation. Although there has been some analysis of overall infection rates in arthropods and within individual insect orders, there has been little exploration of within‐species variation. In this study, primers specific for the ftsZ gene of Wolbachia were used to amplify it from different geographical samples of the European raspberry beetle ( Byturus tomentosus ), confirming the presence of Wolbachia . More than 99% of UK individuals were found to be infected with Wolbachia and 97% of these B. tomentosus beetles harboured multiple infections. Preliminary analysis of B. tomentosus beetles from continental European populations revealed a lower level of infection (24%) than those from the UK. Phylogenetic analysis using the ftsZ DNA sequences places Wolbachia from B. tomentosus into a new clade (Abt) within the A division, with some revisions to the existing Wolbachia phylogeny.

A polymorphic microsatellite marker in the rat major histocompatibility complex class I gene, RT1.M4 , and a new recombinant RT1 haplotype, r39 - D. Lambracht-Washington; Hayase Shisa; Geoffrey W. Butcher; Kirsten Fischer Lindahl (Immunogenetics, 1998)

Field predation of twospotted spider mite in a New Zealand strawberry crop - M. R. Butcher; D. R. Penman; R. R. Scott (BioControl, 1988)

Evidence for a possible regulatory gene (Suc-1) controlling sucrase expression in mouse intestine - P. S. James; M. W. Smith; G. W. Butcher; D. Brown; E. K. Lund (Biochemical Genetics, 1986)

The electrophoretic analysis of low molecular weight nucleic acids from Crohn's disease tissues in the search for an unconventional small infections agent - P. D. Butcher; J. J. McFadden; J. Hermon-Taylor (Archives of Virology, 1986)